The transition from a-level to under-graduate geography: a focus on Midlands State University, Zimbabwe - Jerie, Steven; Mangizvo, Remmigio (International Research Journals, 2016)
http://www.interesjournals.org/full-articles/the-transition-from-a-level-to-under-graduate-geography-a-focus-on-midlands-state-university-zimbabwe.pdf?view=inline